The Influence of the Project Based Learning Model in the Edu Entrepreneur Course on Student Creativity - Fitri Aisyah; Ranti Firdaus; Afrina Refdianti (Journal of Social Knowledge Education (JSKE), 2026)
Purpose of the study: The primary aim of this study is to determine the influence of the Project Based Learning (PjBL) model on the creativity of Arabic Language Education students. It specifically evaluates how implementing practical projects in the Edu Entrepreneur course stimulates innovative thinking and aligns with higher education performance standards. Methodology: This research utilizes a quantitative approach with a Pre-Experimental One-Group Pretest-Posttest Design. Data were collected from 23 students selected through purposive sampling. Instruments include the Creative Thinking Scale (CTS) and observation sheets for product assessment. Analysis was performed using SPSS software, applying descriptive statistics and Paired Sample T-Tests. Main Findings: The findings reveal a significant increase in creativity scores, rising from a pre-test mean of 72.71 to a post-test mean of 88.50, reaching the "very high” category. The Paired Sample T-Test resulted in a significance value of 0.000, proving that the PjBL model effectively enhances student creativity. Students successfully transformed language theories into innovative Arabic learning media with economic potential. Novelty/Originality of this study: This study introduces the integration of PjBL specifically within an Arabic Edu Entrepreneurship framework, addressing the gap in language-based entrepreneurial education. It advances existing knowledge by demonstrating how a student-centered "protagonist" approach fulfills Indikator Kinerja Utama (IKU) 7, bridging the gap between linguistic competence and practical entrepreneurial innovation.